ANALISIS PREDIKSI KEBANGKRUTAN PADA PT PUPUK INDONESIA (PERSERO) MENGGUNAKAN MODEL ALTMAN Z-SCORE, SPRINGATE & ZMIJEWSKI - Willem Petrus Riwu; Sonny Taufan; Alif Rizkiawan; Marison Sitorus (KALBISCIENTIA Jurnal Sains dan Teknologi, 2023)
PT Pupuk Indonesia (Persero) is a state-owned company engaged in agrochemicals, petrochemicals and agrotechnology. Like other companies, PT Pupuk Indonesia (Persero) was also affected by several major events that have occurred in the world recently, one of which is the Covid-19 Pandemic, whose effects can be felt to this day. This study aims to determine the level of company bankruptcy after running a business under pandemic conditions such as in 2020. This research uses an analytical tool in the form of the Altman Z-Score, Springate & Zmijewski Model.